EVALUATION OF A BODY CHECKING POLICY CHANGE AS AN INJURY PREVENTION STRATEGY FOR NON-ELITE YOUTH ICE HOCKEY PLAYERS. Issue 7 (11th March 2014) - Emery, CA; Black, A; Macpherson, A; Kang, J; Hagel, B; Romiti, M; Meeuwisse, W
Abstract : Background: In Pee Wee (ages 11–12) ice hockey, body checking is associated with an increased risk of injury and concussion. In 2011, research informed some provincial policy change, disallowing body checking in non-elite Pee Wee leagues. Objective: To determine if the risk of injury and concussion differ for non-elite Pee Wee ice hockey players in leagues where body checking is permitted (Alberta, Canada) compared to leagues where prospective policy change disallows body checking (Ontario, Canada). Design: Cohort study. Setting: Ice hockey rinks (2011/12 season). Participants: Non-elite (lower 70%) Pee Wee ice hockey players from Alberta (n=590) and Ontario (n=281). Risk factor assessment: Exposure to a Pee Wee league where policy permits body checking. Other risk factors included previous concussion/injury, year of play, level of play, position and attitudes toward body checking. Main outcome Measurement: Suspected concussions were identified by a team designate and referred to a sport medicine physician. Hockey injuries included those requiring medical attention or time loss. Results: There were 101 game injuries (incidence rate [IR]=4.19/1000 game hours [95% CI; 3.38–5.18]), and 67 game concussions ([IR]=2.78/1000 game hours [95% CI; 2.19–3.52]) in Alberta and 14 game injuries (IR=1.60/1000 game hours [95% CI; 0.87–2.94]) and 8 concussions (IR=0.91/1000 game hours [95% CI; 0.41–2.06]) in Ontario. Based on multivariate poisson regression (adjusted for cluster, exposure hours and other risk factors), incidence rate ratio associated with policy allowing body checking was 2.97 (95% CI; 1.33–6.61) for game injury and 2.83 (95% CI; 1.09–7.31) for concussion. Conclusions: The risk of injury and concussion was 3-fold greater in non-elite Pee Wee hockey players in leagues where body checking is permitted. This is similar to previous findings examining retrospective policy change. Policy change disallowing body checking is effective in preventing injury and concussion in non-elite youth ice hockey.